Petrology, Geochemistry, and Magma Evolution Of Basaltic Rocks Of Baturraden Area, Central Java, Indonesia. - Prasetya, Yogi Adi; Gibran, Akhmad Khahlil; Aziz, Mochammad; Siswandi (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Slamet volcano is the second highest active stratovolcano in Java Island, it has a long volcanic history eruption event, the Baturraden Area is a tourism area in southern part of Slamet Volcano. Baturraden area is the part of Banyumas Regency and it took 30-60 minutes riding motorcycle from Purwokerto city. Our research is focused on studying the petrology, geochemistry, and geological history of basaltic lava on Baturraden Area mainly that formed a waterfall on its location, because there is no a researcher that study basaltic lava on Baturraden, we focus on petrology, and petrography and geochemistry of basaltic lava on Baturraden using XRF methods and focused on magma evolution of basaltic lava rocks on Baturraden Area. Stratigraphically basaltic rocks in Baturraden Area are a part of Slamet Lava 1(SL 1) and Slamet Lava 2 (SL 2). The mineral composition of SL 1 and SL 2 are including the phenocryst of plagioclase, K-feldspar, olivine, clinopyroxene, and opaque minerals, with plagioclase microlites and volcanic glass as groundmass. Plagioclase shows zoning and sieve texture. Seven rock samples are prepared for whole-rock major element compositions of the study, the SiO2 contents range from 48.13 – 49.17 wt.%. The K2O contents in all rock samples range from 0.78 – 1.56 wt.%. Geochemical data confirm that SL 1 and SL 2 are from same magma type that magma of SL  1 and SL 1 are influenced by fractional crystallization and magma mixing from new injection of more basaltic magma, as evidenced by the frequent changes in SiO2 content.